Effects of Melatonin on the Defense to Acute Hypoxia in Newborn Lambs - Beñaldo, Felipe A.; Llanos, Aníbal J.; Araya-Quijada, Claudio; Rojas, Auristela; Gonzalez-Candia, Alejandro; Herrera, Emilio A.; Ebensperger, Germán; Cabello, Gertrudis; Valenzuela, Guillermo J.; Serón-Ferré, María (Frontiers in Endocrinology, 2019)
Neonatal lambs, as other neonates, have physiologically a very low plasma melatonin concentration throughout 24 h. Previously, we found that melatonin given to neonates daily for 5 days decreased heart weight and changed plasma cortisol and gene expression in the adrenal and heart. Whether these changes could compromise the responses to life challenges is unknown. Therefore, firstly, we studied acute effects of melatonin on the defense mechanisms to acute hypoxia in the neonate. Eleven lambs, 2 weeks old, were instrumented and subjected to an episode of acute isocapnic hypoxia, consisting of four 30 min periods: normoxia (room air), normoxia after an i.v. bolus of melatonin (0.27 mg kg−1, n = 6) or vehicle (ethanol 1:10 NaCl 0.9%, n = 5), hypoxia (PaO2: 30 ± 2 mmHg), and recovery (room air). Mean pulmonary and systemic blood pressures, heart rate, and cardiac output were measured, and systemic and pulmonary vascular resistance and stroke volume were calculated. Blood samples were taken every 30 min to measure plasma norepinephrine, cortisol, glucose, triglycerides, and redox markers (8-isoprostane and FRAP). Melatonin blunted the increase of pulmonary vascular resistance triggered by hypoxia, markedly exacerbated the heart rate response, decreased heart stroke volume, and lessened the magnitude of the increase of plasmatic norepinephrine and cortisol levels induced by hypoxia. No changes were observed in pulmonary blood pressure, systemic blood pressures and resistance, cardiac output, glucose, triglyceride plasma concentrations, or redox markers. Melatonin had no effect on cardiovascular, endocrine, or metabolic variables, under normoxia. Secondly, we examined whether acute melatonin administration under normoxia could have an effect in gene expression on the adrenal, lung, and heart. Lambs received a bolus of vehicle or melatonin and were euthanized 30 min later to collect tissues. We found that melatonin affected expression of the immediate early genes egr1 in adrenal, ctgf in lung, and nr3c1, the glucocorticoid receptor, in adrenal and heart. We speculate that these early gene responses may contribute to the observed alterations of the newborn defense mechanisms to hypoxia. This could be particularly important since the use of melatonin is proposed for several diseases in the neonatal period in humans.